2019
DOI: 10.1002/jcp.28486
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of a novel lncRNA LOC105369748 suppresses the progression of hepatocellular carcinoma by sponging miR‐5095 from MBD2

Abstract: A growing number of studies have suggested that long noncoding RNAs (lncRNAs) play critical roles in human malignant cancers, including hepatocellular carcinoma (HCC). However, the functions of most lncRNAs have not been elucidated in HCC. In the present study, we explored the potential functions of a novel lncRNA LOC105369748 in the HCC progression. We identified that LOC105369748 expression was significantly elevated in HCC tissues compared with normal tissues based on bioinformatics analysis, quantitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…24 LOC105369748 upregulates MBD2 through binding to miR-5095, which conveys oncogenic signals to accelerate the carcinogenesis and progression of hepatocellular carcinoma. 25 All above evidence indicates an oncogenic role of MBD2 in the initiation and progression of cancers. However, the pathophysiologic function and regulatory mechanism of MBD2 in RCC remain largely unknown.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…24 LOC105369748 upregulates MBD2 through binding to miR-5095, which conveys oncogenic signals to accelerate the carcinogenesis and progression of hepatocellular carcinoma. 25 All above evidence indicates an oncogenic role of MBD2 in the initiation and progression of cancers. However, the pathophysiologic function and regulatory mechanism of MBD2 in RCC remain largely unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Aberrant DNA methylation modifications are frequently detected in various tumors, and the main mechanisms for DNA methylation-involved tumorigenesis are that methylation levels of the promoter region of anti-oncogene are elevated, which promotes the key anti-oncogene silencing and drives tumorigenesis. 12,[14][15][16] MBD2 has been reported in multiple human malignancies, including gastric cancer, 17 breast cancer, 18,19 colorectal cancer, 20 glioblastoma, 21,22 hilar cholangiocarcinoma, 23 hepatocellular carcinoma, 24,25 chronic myeloid leukemia 26 and prostate cancer. 27 Previous studies confirmed that MBD2 mediates the transcriptional repression of tumor suppressor genes, such as hTERT, 28 GSTP1, 29 BAI1, 21 p14 ARF /p16 INK4a,30 and 14-3-3sigma, 27 which supports the pivotal role of MBD2 in abnormal epigenetic regulation of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, maximum radical resection of the tumor and reduction of residual cancer tissue are essential to improve the prognosis of HGSOC. In addition, the expression level of MBD2 in HCC is higher compared with that in normal tissues ( 51 ). MBD2 is an independent prognostic factor that affects the overall survival and disease-free survival of patients and is considered to be a potential clinical prognostic marker ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have unveiled several lncRNAs that play oncogenic or tumor-suppressive roles in HCC. For instance, a lncRNA named LOC105369748 was found to overexpress in HCC tissues and further promote the proliferation, migration, invasion, and epithelial-to-mesenchymal transition of HCC cells [10]. Similarly, FLVCR1 antisense RNA 1 (FLVCR1-AS1) is another lncRNA was reported to be up-regulated in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%